Progression of geographic atrophy in age-related macular degeneration imaged with spectral domain optical coherence tomography - Yehoshua, Zohar; Rosenfeld, Philip J; Gregori, Giovanni; Feuer, William J; Falcão, Manuel; Lujan, Brandon J; Puliafito, Carmen (Ophthalmology (Rochester, Minn.), 2011)
To determine the area and enlargement rate (ER) of geographic atrophy (GA) in patients with age-related macular degeneration (AMD) using the spectral domain optical coherence tomography (SD-OCT) fundus image. Prospective, longitudinal, natural history study. Eighty-six eyes of 64 patients with ≥6 months of follow-up. Patients with GA secondary to AMD were enrolled in this study. Macular scans were performed using the Cirrus SD-OCT (Carl Zeiss Meditec, Dublin, CA). The areas of GA identified on the SD-OCT fundus images were quantified using a digitizing tablet. Reproducibility of these measurements was assessed and the ER of GA was calculated. The usefulness of performing square root transformations of the lesion area measurements was explored. Enlargement rate of GA. At baseline, 27% of eyes had a single area of GA. The mean total area at baseline was 4.59 mm(2) (1.8 disc areas [DA]). The mean follow-up time was 1.24 years. Reproducibility, as assessed with the intraclass correlation coefficient (ICC), was excellent on both the original area scale (ICC = 0.995) and the square root scale (ICC = 0.996). Intergrader differences were not an important source of variability in lesion size measurement (ICC = 0.999, 0.997). On average, the ER of GA per year was 1.2 mm(2) (0.47 DA; range, 0.01-3.62 mm(2)/year). The ER correlated with the initial area of GA (r = 0.45; P<0.001), but there were variable growth rates for any given baseline area. When the square root transformation of the lesion area measurements was used as a measure of lesion size, the ER (0.28 mm/yr) was not correlated with baseline size (r = -0.09; P = 0.40). In this cohort of lesions, no correlation was found between ER and length of follow-up. Square root transformation of the data helped to facilitate sample size estimates for controlled clinical trials involving GA. The SD-OCT fundus image can be used to visualize and quantify GA. Advantages of this approach include the convenience and assurance of using a single imaging technique that permits simultaneous visualization of GA along with the loss of photoreceptors and the retinal pigment epithelium that should correlate with the loss of visual function.